The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2011
DOI: 10.1002/dneu.20842
|View full text |Cite
|
Sign up to set email alerts
|

EphA4 and ephrin‐B2 expression patterns during inferior colliculus projection shaping prior to experience

Abstract: Central processing of complex auditory tasks requires elaborate circuitry. The auditory midbrain, or inferior colliculus (IC), epitomizes such precise organization, where converging inputs form discrete, tonotopically-arranged axonal layers. Previously in rat, we established that shaping of multiple afferent patterns in the IC central nucleus (CNIC) occurs prior to experience. This study implicates an Eph receptor tyrosine kinase and a corresponding ephrin ligand in signaling this early topographic registry. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
41
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 18 publications
(48 citation statements)
references
References 70 publications
6
41
1
Order By: Relevance
“…Eph proteins, including the Eph receptors and their ligands, the ephrins, are broadly expressed in the developing auditory system (for reviews see Bianchi et al, 2002, Pickles, 2003, Cramer, 2005, Gabriele et al, 2011). They provide multiple mechanisms for signaling and for generating precise connectivity.…”
Section: Eph Receptors and Ephrinsmentioning
confidence: 99%
See 2 more Smart Citations
“…Eph proteins, including the Eph receptors and their ligands, the ephrins, are broadly expressed in the developing auditory system (for reviews see Bianchi et al, 2002, Pickles, 2003, Cramer, 2005, Gabriele et al, 2011). They provide multiple mechanisms for signaling and for generating precise connectivity.…”
Section: Eph Receptors and Ephrinsmentioning
confidence: 99%
“…An important first step in assessing whether Eph/ephrins play an instructive role in auditory midbrain map formation is the identification of protein expression patterns that correlate with the early period of projection shaping (Figure 3). Localization studies utilizing immunocytochemical and X-Gal staining approaches in lacZ mutants show a transient expression of EphA4 and ephrin-B2 in the IC leading up to the functional onset of hearing (Gabriele et al, 2011). In rat and mouse, each is expressed in a graded fashion across the tonotopic axis of the CNIC, with protein most concentrated in ventromedial, high-frequency regions.…”
Section: Auditory Midbrainmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies from our laboratory revealed discrete afferent patterns in the central nucleus and lateral cortex of the IC (CNIC and LCIC, layered and modular, respectively) in a variety of species (Gabriele et al, 2000a,b, 2007, 2011; Henkel et al, 2005; Fathke and Gabriele, 2009). Similarly to inputs arising from the cochlear nuclei and nuclei of the lateral lemniscus (Oliver, 1984, 1987; Kandler and Friauf, 1993; Oliver et al, 1997; Gabriele et al, 2000a,b; Fathke and Gabriele, 2009), the lateral superior olive (LSO) sends bilateral layered projections to the CNIC (Shneiderman and Henkel, 1987; Gabriele et al, 2007; Fathke and Gabriele; 2009).…”
mentioning
confidence: 97%
“…In comparison with the CNIC, the LCIC receives less subcollicular input. However, recently we reported a patchy projection in rat and mouse to deep portions of the LCIC arising from the ipsilateral LSO (Gabriele et al, 2011). The input is robust and terminates in a series of discontinuous modules that span the rostrocaudal dimension of the LCIC.…”
mentioning
confidence: 98%